Pengaruh Layanan Konseling Kelompok dengan Teknik Expressive Writing untuk Menurunkan Prilaku Self Injury pada Siswa : The Effect of Group Counseling Services with Expressive Writing Techniques to Reduce Self-Injury Behavior in Students - Putri Aulia Medy; Alfin Siregar (ITScience (Information Technology and Science), 2024)
This study aims to analyze the effect of Group Counseling with expressive writing techniques to reduce self-injury behavior in students at SMP Negeri 35 Medan. So, based on the problem, this study aims to determine the effect of group counseling services with expressive writing techniques in reducing self-injury behavior. The method used in this study is quantitative research using a pre-experimental design, with the design form used being a one-group pretest-posttest design. This research was conducted at SMP Negeri 35 Medan. The study population was 60 students in class VIII, and the sample was taken using purposive sampling. Data analysis using the Wilcoxon Signed Rank Test obtained an asymp. A Sig (2-tailed) value smaller than 0.05, which is 0.011, means that group counseling with expressive writing techniques effectively prevents self-injury behavior in students. The results of this study indicate that Self-injury behavior has changed after being given group counseling services with the expressive writing technique. However, it does not prevent self-injury behavior from occurring one hundred percent; it can at least reduce self-injury behavior carried out by students themselves. The level of tendency of Self-injury behavior before being given counseling services. There is a significant difference between the tendency of self-injury behavior in students before and after being given treatment using the expressive writing technique using group counseling services. The posttest score is lower than the pretest score.